Cutaneous Leukocytoclastic Vasculitis in Jose R. Reyes Memorial Medical Center: A 12 year Retrospective Study - Bajracharya, S.; Ismael, D.K.; Venida, M.L.A. (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
Introduction: Leukocytoclastic vasculitis (LCV) is the commonest vasculitis of skin affecting small vessels. Objectives: To study epidemiology, etiology, clinical and laboratory features and treatment outcomes in LCV patients. Material and methods: This is a Hospital based retrospective analytical study where cases with histological evidence of LCV were collected from pathology database since January 2000 to December 2011. Records were analyzed for variables, clinical features, etiological factors, laboratory results, and treatment outcome. Results: Of total 98 cases, 70 (71.43%) were Female and 28(28.57%) Male. Mean age was 28.35 years (range 1 to 71 years). Palpable purpura was commonest presentation (74.49%) involving mostly lower limbs (91.84%). Commonest symptom was abdominal pain (27.55%), followed by arthralgia (25.51%) and pruritus (24.49%). Majority of cases had unknown etiology (69.07%). Those with documented etiology included infection (25.51%) and drugs (5.10%). Leukocytosis was commonest laboratory abnormality. Forty one percentage of patients had complete remission, 33% improved, 2 % deteriorated and 24% were lost to follow up. Conclusion: Females were more affected. Palpable purpura in lower limb was commonest presentation. Majority were idiopathic LCV. Amoxicillin and UTI were commonest among causes of drugs and infection, respectively. Commonest abnormality was leukocytosis. The majority of the cases improved with therapy. Nepal Journal of Dermatology, Venereology & Leprology, Vol.14(1) 2016, pp.18-24